Rabbit redux - Updike, John (Fawcett Columbine, 1996)
The assumptions and obsessions that control our daily lives are explored in tantalizing detail by master novelist John Updike in this wise, witty, sexy story. Harry Angstrom--known to all as Rabbit, one of America's most famous literary characters--finds his dreary life shattered by the infidelity of his wife. How he resolves--or further complicates--his problems makes a compelling read.